Smarketing Strategies of Minang Indo Jalito Handicraft Business in Nagari Pandai Sikek, Kec. X Koto, Tanah Datar Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The purpose of this study is to analyze the marketing strategy of minang indo jali to handicraft businessin Nagari Pandai Sikek, X Koto District, Tanah Datar Regency. Related research methods used are descriptive qualitative research methods, through observation, interviews, and documentation with SWOT analysis. The results of the study show that handicrafts in Nagari PandaiSikek have diversity, but there is one of the many handicraft businesses there, namely Minang Indo Jalito. Minangindojalito handicrafts have uniqueness, this uniqueness can be seen from the results of handicraft production, such as woven fabrics, party bags combined with songket fabric, embroidery, suji, clutchbags, embroidery clutchbags and many others, the design of these handicrafts is based on the times, so that the crafts in produksi are not outdated. In marketing its handicraft products, Minang Indo Jalito uses Facebook as an internet media in promoting its trade goods, as well as using other internet media.